Pete the cat's train trip ebook - Dean, James (My First I Can Read: Pete the Cat., 2015)
New York Times bestselling author and artist James Dean brings young readers along on a groovy train ride with Pete the Cat! Pete can't wait to visit Grandma, especially because he gets to take a train ride to see her! The conductor gives Pete a tour of the train, and Pete gets to see the engine and honk the horn. Pete even makes new friends and plays games on board. What a cool ride! Pete the Cat's Train Trip is a My First I Can Read Book, which means it's perfect for shared reading with a child. Fans of Pete the Cat will delight as Pete takes the grooviest train trip in this hilarious I Can Read adventure.